Nanocomposite silica surfactant microcapsules by evaporation induced self assembly: tuning the morphological buckling by modifying viscosity and surface charge - Sen, D.; Bahadur, Jitendra; Mazumder, S.; Verma, G.; Hassan, P. A.; Bhattacharya, S.; Vijai, K.; Doshi, Pankaj (Soft Matter, 2012)
Nanocomposite microcapsules of silica and surfactants have been synthesized using evaporation induced self-assembly through spray drying. It was established using electron microscopy and small-angle neutron/X-ray scattering experiments that the viscosity of the virgin dispersion and surface charge of colloidal components play a significant role in the buckling of spray droplets during drying. Hollow spherical grains are realized at relatively low viscosity and higher surface charge while mushroom like grains manifest at higher viscosity and lower surface charge. In the intermediate conditions, deformed doughnut shaped microcapsules are obtained. Scattering experiments establish the presence of the organization of micelle like aggregates of surfactants in the dried grains and also corroborate with the observations from electron microscopy. A plausible mechanism regarding the chronological pathways of morphological transformation is illustrated. Computer simulation, based on buckling of an elastic shell using a surface evolver, has been attempted in order to corroborate the experimental results.

Multi-walled CNT-induced phase behaviour of poly(vinylidene fluoride) and its electro-mechanical properties - Rath, Sangram K.; Dubey, Sachin; Kumar, G. Sudheer; Kumar, Sanjay; Patra, A. K.; Bahadur, Jitendra; Singh, A. K.; Harikrishnan, G.; Patro, T. Umasankar (Journal of Materials Science, 2014)
A simple two-step process was used to disperse acid functionalizedmulti-walled carbon nanotubes (CNTs) in poly(vinylidene fluoride) (PVDF). While the neat solvent-cast PVDF showed coexistence of alpha- and beta-phases; the composite films exhibited only beta-phase crystals. Further studies on the crystalline behaviour, using differential scanning calorimetry and small-angle X-ray scattering techniques showed an increase in the percentage of crystalline phase with CNT. The network formed by CNTs in the matrix reduced the macroscopic electrical resistivity of composite films. The dielectric constant increased with CNT loading. Further, these composites were investigated for its electromagnetic wave absorbance (EWA) and strain sensing properties. The EWA properties were studied in the X-band (6-12 GHz) region. A maximum of similar to 37 dB reflectivity loss at similar to 9.0 GHz was obtained in a similar to 25 mu m thick PVDF film containing only 0.25 wt% of functionalized CNT. Preliminary studies showed a systematic change in electrical resistance by the application of dynamic bending strain in nanocomposite film. The film also showed a significant improvement in mechanical stiffness owing to efficient stress transfer from matrix to filler, the property desirable for a good strain sensor. In view of the unique combination of EWA and electro-mechanical properties, the nanocomposite films are expected to serve as a multifunctional material for strain sensing in health monitoring as well as in radar absorption.

Highly stable In-SBA-15 catalyst for vapor phase Beckmann rearrangement reaction - Kumar, Rawesh; Shah, Sneha; Bahadur, Jitendra; Melnichenko, Yuri B.; Sen, Debasis; Mazumder, S.; Vinod, Chathakudath P.; Chowdhury, Biswajit (Microporous and Mesoporous Materials, 2016)
The Indium doped SBA-15 material was prepared by sol-gel method and tested for vapor phase Beckman rearrangement reaction. Among three indium loading, In/Si ratio of 2/100 was found as an optimum composition in terms of caprolactam selectivity (100%) and cyclohexanone oxime conversion (100%). The catalysts were characterized by N-2 adsorption, small-angle X-rays/neutron scattering (SAXS/SANS), XRD, FESEM, HRTEM, EDX, UV, FTIR and NH3-TPD techniques. In-situ SANS experiment was performed on the adsorption of CO2 to detect the micropores in the mesopore wall. All catalysts samples have highly ordered hexagonal structure with well dispersed indium in the silica matrix. The fine tuning of weak and strong acid sites were found in indium doped SBA-15 (In/Si = 2/100) catalyst. The same catalyst showed optimum catalytic performance, high space time yield 114.4 mol/h/g(cat) and high stability till 6 h of reaction without deactivation. The micro-kinetic analysis showed that there were no external and internal diffusion limitations in the SBA-15 catalyst. The reaction mechanism of Beckmann rearrangement over In-SBA-15 has been elucidated. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: e-Caprolactam; In-situ SANS; indium; SAXS; SBA-15